2022
DOI: 10.1002/app.52646
|View full text |Cite
|
Sign up to set email alerts
|

Influence of process parameters on the formation of inhalable fiber dust during shredding for mechanical recycling of fiber‐reinforced organo sheets

Abstract: Shredding is a major process step in mechanical recycling, as the plastic scrap needs to be cut into small pieces for further processing. It will be melted and finally injection‐molded to form new plastic parts. Also for fiber‐reinforced thermoplastics, the mechanical recycling process is an ecofriendly process because all resources are reused. One challenge during the shredding of fiber‐reinforced plastics is the fiber dust formation. The fiber dust disturbs the following production processes, and the fiber f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…Therefore, the particle-particle interaction in the cutting chamber is enhanced, which could be a reason why the favorable effect of the smaller feedstock size can just slightly be seen in the fiber length in Figure 2. In a similar investigation, Shuaib and Mativenga [22] also found no significant effect of the feedstock size on the fiber length and in [23] it was found that the effect of the feedstock size on the particle mass and the fiber length is material dependent.…”
Section: Effect Of Shredding Parameter On Fiber Dust Formationmentioning
confidence: 85%
“…Therefore, the particle-particle interaction in the cutting chamber is enhanced, which could be a reason why the favorable effect of the smaller feedstock size can just slightly be seen in the fiber length in Figure 2. In a similar investigation, Shuaib and Mativenga [22] also found no significant effect of the feedstock size on the fiber length and in [23] it was found that the effect of the feedstock size on the particle mass and the fiber length is material dependent.…”
Section: Effect Of Shredding Parameter On Fiber Dust Formationmentioning
confidence: 85%
“…Also for occupational exposure situations, the number of published studies is surprisingly small. Studies on the release of respirable fragments from CF or CFRP include [8,23,24,[31][32][33][34][35][36][37][38][39][40][41][42]. The authors of [7,35] observed submicron fibers from machined nano-and microscale fiber composites, whereas earlier works reported that the original fiber diameters were maintained even during very different machining operations [33].…”
Section: Introductionmentioning
confidence: 99%